2020
DOI: 10.1039/d0cc05963c
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization relaxation dynamics of a rare coordinatively unsaturated Co(ii) complex: experimental and theoretical insights

Abstract: A robust and an unusual three coordinate Co(II) complex [Li(DME)3] [Co(L)3] (1, where L = Lithium (2,6-diisopropylphenyl) amide and DME = Dimethoxyethane) shows an easy plane magnetic anisotropy (D) which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The highest pseudo symmetry point group of D3h or C3v in this class of molecules has a unique principle axis which can generate magnetic anisotropy. A quick Cambridge structural database search reveals a report of 140 three-coordinate Co complexes with various donor atoms exemplifying the versatility, 40,41 Although there are several correlations and design clues offered for various Co SIMs with a coordination number starting from four 14 , to the best of our knowledge, such an endeavour is missing for three coordinate Co complexes, despite its potential.…”
Section: Introductionmentioning
confidence: 99%
“…The highest pseudo symmetry point group of D3h or C3v in this class of molecules has a unique principle axis which can generate magnetic anisotropy. A quick Cambridge structural database search reveals a report of 140 three-coordinate Co complexes with various donor atoms exemplifying the versatility, 40,41 Although there are several correlations and design clues offered for various Co SIMs with a coordination number starting from four 14 , to the best of our knowledge, such an endeavour is missing for three coordinate Co complexes, despite its potential.…”
Section: Introductionmentioning
confidence: 99%
“…7 Great effort is devoted to constructing SIMs with low coordination numbers, low oxidation states and high symmetry because of their strong magnetic anisotropy. 8,9 A record energy barrier of 450 cm −1 was found for a two-coordinate linear Co( ii )-SIM, Co(C(SiMe 2 ONaph) 3 ) 2 (Me = methyl, Naph = naphthyl group). 8 a However, low-coordinate SIMs are usually unstable and difficult to prepare.…”
Section: Introductionmentioning
confidence: 99%
“…[82][83][84][85] Thus, for example, Shanmugam and co-workers have demonstrated that the halide ion plays a pivotal role in determining the sign and magnitude of the D parameter. [86][87][88][89][90] This approach has also been utilized by other research groups. [91][92][93][94][95][96] Moreover, along with the ligand field strength arising from the first coordination sphere of the transition metal ions, the secondary effects imposed by counter anions/cations can also affect the D parameter.…”
Section: Introductionmentioning
confidence: 99%